The Qur’an and the Intellectual and Moral Development of Youth: In the Context of Contemporary Challenges - Naeem Anwar Khan; Siddiqu Ullah (Journal of Religion and Society, 2026)
The modern generation is faced with heavy intellectual and moral issues, such as confusion of ideologies, moral decay, materialism, adverse effects of digital media, identity crisis and value confusion. In such a situation, intellectual and moral growth of the youth has become a key academic and social issue. This paper discusses the principles of intellectual and moral training on youth as described in the Quran and evaluates its usefulness and practicality in overcoming modern day challenges. The Quran shows human beings as being endowed to reason, moral responsibility and conscious choice but acknowledges the youth as the stage of decisional personality formation. Some of the main Quranic principles that are critically examined in this research include development of intellect and reflection, cleansing of self (tazkiyah), ethical principles, moderation, self responsibility, meaning of life and community accountability. Besides this, it provides a critical evaluation of contemporary intellectual problems, such as secularism, atheism, consumerism, moral relativism, and digital culture, to prove how these problems shape the beliefs, behavior, and moral perspective of the youth. This paper will follow the qualitative research approach, which relies on the interpretation of the verses of the Quran, ancient and modern exegeses, and other available contemporary academic literatures. The results show that the Quran offers a comprehensive, coherent and sustainable approach to the intellectual and moral growth of youth both in the individual character building as well as in the social change of the society. Moreover, the cultural interpretation of the Quranic system can provide the youth with intellectual comprehension, moral acumen, and high sense of societal duty which is critical towards the creation of a well-balanced, ethical and dignified society in the contemporary world. Keywords: Qur’anic Education, Youth Intellectual Development, Moral and Ethical تربیت, Contemporary Challenges, Digital Culture and Ethics, Islamic Moral Framework, Character Building in Islam